Hypoxia lowers cell carbon and nitrogen content and accelerates sinking of a marine diatom Thalassiosira pseudonana - Chen, Bokun; Song, Hui; Xu, Ge; Ji, Hongli; Yang, Xue; Li, Gang (Frontiers in Marine Science, 2025)
The positive or negative effect of a decrease in dissolved O2 on the photophysiology of phytoplankton is determined by the duration of light exposure. To uncover the underlying mechanisms, the marine model diatom Thalassiosira pseudonana was cultured under three dissolved O2 levels (8.0 mg L-1, ambient O2; 4.0 mg L-1, low O2; and 1.3 mg L-1, hypoxia) to compare its growth, cell composition, and physiology between the light and dark periods. The results showed that the growth rate under ambient O2 was 0.60 ± 0.02 day-1, which was half of the growth rate during light period and 15-fold of the growth rate during dark period. Decreasing O2 increased the growth rate during light period but decreased it during dark period and decreased the cell pigment content in both the light and dark periods. In the light, low O2 increased cell carbon (C) content, while hypoxia decreased it, with the degree of increase and decrease being greater in the dark. Low O2 had no significant effect on cell nitrogen (N) content, but hypoxia decreased it. Low O2 had no significant effect on photosynthetic efficiency but decreased the dark respiration rate. In darkness, low O2 had no significant effect on cell C loss rate but decreased N loss rate, leading to an increase in the POC/PON ratio. In addition, hypoxia exacerbated cell mortality and sinking, suggesting that diatom-derived carbon burial may be accelerated due to marine deoxygenation in the future.